Death and traslation on Pascal Quignard writing - Melina Balcázar Moreno (Acta Poética, 2015)
This article explores the facet of the writer Pascal Quignard as a translator and his point of view about an impossible task. Rather than engaging in a dialogue with his time, to bring the words of another language to yours, Quignard assumes that translation is a relationship with death and the dead. "Translating is to help people talk to the dead", writes Quignard, and from where we start to show how he approaches problems dealing with bonding and rivalry of translation, touching at the same time what escapes irretrievably to the sense.